The Attitudes of Communication Practitioners in Saudi Newspapers toward Their Professional Practices on Social Media: A Field Study on a Sample of Saudi Journalists - Alenizi, Saleh Zaid (Journal of Posthumanism, 2024)
This study seeks to examine the attitudes of communication agents, specifically journalists working for Saudi newspapers, toward their professional engagement on social media platforms in light of the diverse challenges and opportunities shaping the professional practices of Saudi journalists. The study aims to provide a framework for evaluating journalistic performance and assessing the extent to which these journalists adhere to professional standards when working within social media environments. This is particularly important given that the content published on personal accounts typically represents the individual views of journalists, rather than reflecting the editorial orientations of their affiliated news organizations. To achieve these objectives, the study adopted a field survey methodology targeting a sample of practicing Saudi journalists. Descriptive and analytical approaches were used to test the study’s hypotheses and answer its research questions. Furthermore, a correlational research design was employed to examine the relationships between the main variables. The study results revealed several important insights, most notably the relatively high educational, age, and socioeconomic levels among the journalists surveyed, indicating an advanced academic orientation and general professional maturity. This research indicates a tendency toward professional behavior based on extensive experience and high journalistic ethical standards. One of the most prominent trends observed was the prevalence of social content on journalists’ personal social media accounts, reflecting a strong tendency toward community engagement and responsiveness to public issues. The study also found a high level of professional awareness among Saudi journalists regarding the legal and regulatory frameworks governing the use of social media. Importantly, journalists demonstrated a clear distinction between journalistic reporting and opinion, demonstrating a strong commitment to ethical standards and professional objectivity aimed at serving the public interest and promoting societal and cultural development. Despite these positive indicators, the study found weak coordination between journalists and media institutions regarding the dissemination of news on personal social media accounts. This gap was interpreted as evidence of journalists’ professional and editorial independence, free from external influences or institutional restrictions. Furthermore, the study highlighted journalists’ commitment to engaging with their audiences and ensuring that published content respects societal values ​​and norms. Journalists demonstrated professional integrity in their practices, such as accurately attributing sources, maintaining objectivity and neutrality in media coverage, and avoiding bias and discriminatory content. Statistical analysis confirmed a close correlation between journalists’ adherence to their newspapers’ editorial policies and the clarity of the content published on their personal accounts. Furthermore, no significant differences were observed in journalists’ engagement with official newspaper accounts across age groups or income levels.